2014
DOI: 10.5114/ceji.2014.42132
|View full text |Cite
|
Sign up to set email alerts
|

Serial ImmuKnow assay in stable kidney transplant recipients

Abstract: ObjectivesThe ImmuKnow assay (cylex Inc., Columbia, MD) has been reported to measure the global immune monitoring tool for organ transplantation recipients. We assess immuKnow ATP values in stable kidney transplant patients.Material and methodsPatients who were kidney transplanted between September 2008 and May 2011 were enrolled in the prospective serial ImmuKnow assay study. The criteria of inclusion were living donor kidney transplantation (KT), no evidence of hepatitis B virus (HBV) and hepatitis C virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, our study had the limitations of a retrospective study from a single centre and the employment of single time point measurements, as well as the risk of potential bias and the effects of confounders. More than 75% of our patients underwent the ImmuKnow assay more than 12 months after transplantation, although the value of ImmuKnow assay was significantly different, depending on the length of time after transplantation within 1 year ; whether the functional immune response differs over time in the late phase requires further investigation. A single result cannot be expected to predict the long‐term immune function of the patient.…”
Section: Discussionmentioning
confidence: 91%
“…However, our study had the limitations of a retrospective study from a single centre and the employment of single time point measurements, as well as the risk of potential bias and the effects of confounders. More than 75% of our patients underwent the ImmuKnow assay more than 12 months after transplantation, although the value of ImmuKnow assay was significantly different, depending on the length of time after transplantation within 1 year ; whether the functional immune response differs over time in the late phase requires further investigation. A single result cannot be expected to predict the long‐term immune function of the patient.…”
Section: Discussionmentioning
confidence: 91%
“…have demonstrated the ability to predict acute rejection by markers of recipient T-cell activity. 16,17 Current literature demonstrates the feasibility of minimizing immunosuppression by using tacrolimus only, and some studies even suggest the viability of removing tacrolimus altogether in some patients who may tolerate it. 18,19 Current science technology do not permit us to identify the patients who would reject their allografts if immunosuppression were to be withdrawn, although advancements in detecting genetic signatures that may be indicative of such tolerance have been made.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by a study that found that strong suppression of NFAT‐regulated genes by cyclosporine was associated with increased risks of infectious and malignant complications during renal transplant follow‐up . However, whether or not this can be generalized to all stages post‐transplantation is not yet clear …”
Section: Future Role For Quantifying Immunosuppression?mentioning
confidence: 96%